Synthesis of Fullerene-Fused Fluorine-Containing Lactones from the Radical Reaction of [60]Fullerene with Fluorinated Phenylacetic Acids - Chen, Xiaolei; He, Shanshan; Shen, Subo; Zhao, Jingwei; Zhang, Jianmin; Zhu, Shizheng (Synthesis, 2012)
A series of fullerene-fused fluorinated lactones were prepared by the manganese(III) acetate mediated radical reaction of [60]fullerene (C60) with fluorinated phenylacetic acids (ArFCH2COOH). Interestingly, the products which contain a 2-fluoro substituent on the benzene ring are mixtures of two stereoisomers due to the stereo and electronic effects of the ortho-fluorine atom.
Keywords: C60-fused lactones; fluorinated phenylacetic acids; manganese(III) acetate; stereoisomers